The Effect of Capital Structure, Liquidity, and Firm Size on Company Value with Profitability as an Interverning Variable - Hasanudin; Nurma Wijareni (Graduate Program Magister Manajemen Pendidikan, 2023)
The purpose of this research is to analyze and obtain empirical evidence of the influence of capital structure, liquidity, and firm size on firm value with profitability as an intervening variable. The population in this study are manufacturing companies in the food and beverage sub-sector that are listed on the Indonesia Stock Exchange in 2018-2022, with a total sample of 24 companies and using a purposive sampling method. Furthermore, data were collected quantitatively using multiple regression using Stata 14.2 software. This study shows that capital structure has a significant negative effect on profitability, liquidity has a positive and insignificant effect on profitability, and firm size has a positive and significant effect on profitability. Capital structure has a positive and significant effect on firm value, liquidity has a negative and significant effect on firm value and firm size has a negative and insignificant effect on firm value. Capital structure has a negative and significant effect on firm value through profitability, liquidity has a positive and insignificant effect on firm value through profitability and firm size has a positive and significant effect on firm value through profitability.